Glass products from the First and Second Gostiny excavations in Tobolsk - Anoshko O.M.; Gilderman A.V. (Вестник археологии, антропологии и этнографии)
The article introduces a collection of glassware from the First and Second Gostiny excavations in Tobolsk. Its general characteristics, and the interpretation of well-preserved and specifically significant objects and their analogies are presented, and their origin is being determined. Referring to historical data, a brief history of the emergence and development of glass production in the Tobolsk province is shown. As a result, it has been found that the Tobolsk collection contains both products from local enterprises and imported ones — domestic, including those imitating western brands, and imported, European ones; the study also traces the change in the attitude of the urban population to objects made of glass. From high-status and rare, only accessible to well-off segments of the society in the 17th — early 18th century, they turned into everyday objects in the 19th century, widespread in the urban environment. Products of European origin, as more expensive and high-quality ones, continued to represent objects of prestigious consumption, sought after to emphasize the one’s high position in society.